Passive users vs. active users : a qualitative investigation of brand page attachment on Facebook : a research report presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Marketing, School of Communication, Journalism and Marketing, Massey University, New Zealand - Goldschagg, Caressa (Massey University, 2022)
Brand attachment is the emotional connection consumers have with a brand and is essential in building lasting brand relations. Of equal importance is the construct of brand page attachment; however, it is a relatively new concept with few available studies in the literature. Using the case of Pams' brand page, a home brand of the supermarket chain New World, this study aimed to identify factors that influence passive brand page users to not engage with the brand page. Semi-structured interviews with six users, three passive and three active, were conducted. The interviews explored brand perception, brand page interaction, and brand page attachment. Thematic analysis indicated a direct link between past negative online experiences and the lack of user participation. Brands need to engage with passive brand page users, practically address their concerns, and so increase their brand page interaction to solidify their brand page attachment; this will lead to stronger brand attachment and a more committed consumer.
Keywords: brand attachment; brand page attachment; brand page interaction; brand image; brand personality; brand trust; 350601 Consumer behaviour